YIELD AND YIELD ATTRIBUTES OF EXTRA-EARLY MAIZE (Zea mays L.) AS AFFECTED BY RATES OF NPK FERTILIZER SUCCEEDING CHILLI PEPPER (Capsicum frutescens) SUPPLIED WITH DIFFERENT RATES SHEEP MANURE - Babaji, Bashir Ahmad; Yahaya, Rilwanu A.; Mahadi, Musa A.; Jaliya, Muhammad M.; Ahmed, Adamu; Sharifai, Aminu I; Kura, Habu N.; Arunah, Uthman L. Arunah1 L.; Ibrahim, Ahmad; Muhammad, Aminu A. (AGRIVITA, Journal of Agricultural Science, 2014)
Field experiment was conducted in 2005 and 2006 to study response of extra-early maize variety (95TZEE-Y1) to rates of NPK (0, 40:20:20, 80:40:40 and 120:60:60 kg N:P2O5:K2O ha-1) and residual FYM (0, 5, 10 and 15 t ha-1 applied to chilli pepper the previous season) in the semi-arid zone of Nigeria.  Randomized complete block design with three replicates was used.  Higher values for soil physical and chemical properties were obtained in plots supplied with manure the previous season with soil from 2006 experiment more fertile than for the first year, hence produced 21% more grain yield. All the applied NPK rates in 2005 and except 40:20:20 ha1 in 2006 had resulted in early maize crop as compared to control.  Husked and de-husked cob and 100-grain weights and grain yield/ha were higher at 120:60:60 kg NPK ha-1.  Maize grown in plot supplied with 15 t FYM ha1 the previous year matured earlier.  Cobs and 100-grain weights and grain yield were highest in plot supplied with 10 t FYM ha1.  The 10t FYM ha-1 had 69% and 68% more grain yield than the control in 2005 and 2006, respectively.  Highest maize yield was obtained at 120:60:60 kg NPK ha-1 or 10t FYM ha-1.  All the parameters measured significantly and positively related to each other when the two years data were combined.